Spatiotemporal hotspot analysis of tuberculosis lost to follow-up cases in Ghana: A district-level study from 2019-2023. - David Ngmenbelle; Baaba Amoa-Saah; Stephen Nimirkpen; Maxwell Adjiabadek Akesem; Jacob Solomon Idan; Aliyu Mohammed (PLoS ONE)
Introduction Despite existing measures to control Tuberculosis (TB), the burden of TB remains a serious challenge in Ghana, with declining treatment success rates over recent years. Lost to Follow-Up (LTFU) has been attributed to this decline. This cross-sectional study aims to employed spatiotemporal analysis, an underutilized approach in this context, to explore areas with high prevalence of LTFUs in order to improve TB treatment success rates. Methods A spatiotemporal analysis was conducted in Ghana using TB LTFU data from 2019-2023 extracted from the District Health Information Management System 2 (DHIMS2). Proportions of LTFU were used for spatial mapping. We adopted the Global Moran's I, LISA and Getis-Ord G* techniques to determine spatial autocorrelation, optimized clusters or outliers and identify hotspot areas respectively. Results A total of 2,887 TB LTFU cases were recorded out of 75,604 TB cases. We observed an initial increase of TB LTFU from 2019 (4.12%) to 2020, and a diminishing trend (5.28% to 3.11%) from 2020 to 2023. The Global Moran's I estimations showed significant spatial clustering of TB LTFU cases from 2019 to 2021, shifting to a more random distribution in 2022 and 2023. High spatial clustering of LTFU were primarily reported in districts within Eastern, Central, and Greater Accra regions across 2019-2023, with clusters in Volta and Ashanti regions in 2021. We identified significant hotspot areas in districts within Greater Accra, Central, and Eastern regions. Conclusions Hotspot areas of TB LTFU were primarily identified in densely populated regions. Strategic plans such as intensive education programs should be implemented to address pertinent issues regarding LTFU in the affected districts. Priorities should be directed towards populated regions, particularly Greater Accra, Central and Eastern regions, to improve TB treatment adherence and outcomes.